2014
DOI: 10.1016/j.jpeds.2014.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Race, Demography, and Health Care Disparities Impact Risk for Intraventricular Hemorrhage in Preterm Neonates

Abstract: Objective To determine whether risk factors associated with Grade (Gr) 2–4 intraventricular hemorrhage (IVH) differs between African ancestry and white subjects. Study design Inborn, appropriate for gestational age (GA) infants with birth weights (BW) 500–1250 grams and exposed to >1 dose of antenatal steroids were enrolled in 24 neonatal intensive care units. Cases had Gr 2–4 IVH and controls matched for site, race and BW range had 2 normal ultrasounds read centrally. Multivariate logistic regression modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 46 publications
2
32
1
2
Order By: Relevance
“…Whether this relates to the racial differences noted in incidence of ICH remains to be determined. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Whether this relates to the racial differences noted in incidence of ICH remains to be determined. 22 …”
Section: Discussionmentioning
confidence: 99%
“…15 In an analysis limited to preterm deliveries similar to the current study, increased incidence of IVH among Blacks was attenuated among women with at least one prenatal visit, implicating racially-differential health care access and utilization. 16 An older study examined the causes and factors of developing PVH/IVH in premature infants and reported that mothers with pregnancy-induced hypertension were less likely to have neonates with PVH/IVH, likely attributable to medication use or obstetrical management. 17 Gestational hypertension most commonly complicated pregnancies among White women in our data and risk for IVH was lower in this group.…”
Section: Commentmentioning
confidence: 99%
“…15 Lower GA and birth weight (BW), male gender, white race, chorioamnionitis, Apgar < 3 at 5 minutes, delivery room resuscitation, surfactant administration, neonatal transport, illness severity, assisted ventilation, disturbances of partial pressure of CO 2 , respiratory distress syndrome and high frequency ventilation have all been reported to increase risk for IVH, while a complete course of ANS, cesarean delivery and preeclampsia decrease the risk for IVH (for review please see Shankaran 29 ).…”
Section: Environmental Factors and Health Care Disparities Are Permismentioning
confidence: 99%
“…30–32 Further, infants of African ancestry mothers are less likely to receive surfactant or assisted ventilation, 33 and IVH-related mortality is two times higher in African ancestry neonates when compared to white preterm infants. 34 A recent large prospective analysis demonstrated that white race decreased risk for grades 2–4 IVH in preterm neonates of 500–1250 g; 29 notably, among white infants but not black neonates, multiple gestation was associated with increased risk of IVH, while higher maternal education was associated with a decreased incidence of hemorrhage. When compared to white neonates, infants of African ancestry less often received ANS exposure and required more vigorous delivery room resuscitation.…”
Section: Environmental Factors and Health Care Disparities Are Permismentioning
confidence: 99%